ANALISA KINIERJA SISTEM SALURAN SISTEM TRANSMISI PADA PT. PLN (Persero) TRAGI PADANG - Asnal Effendi; Arfita Yuana Dewi; Jos Mised Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2021)
The air transmission line is one of the most widely used electric power transmission processes. However, this air transmission line requires a large area as a medium of isolation and is prone to interference because it is located at an altitude, especially interference caused by lightning. Disruption to transmission line can result in obstruction of the supply of electrical energy. Interference with transmission lines has a variety of causes. One of causes of interference is equipment. The aim is to analyze the performance of the Transmission Line system in achieving the reliability of the 150kV based on the reliability index of transmission system at PT. PLN (Persero) Tragi Padang in 2017. From the calculation and analysis it is found that the realibility index of transmission system TLOD ( Transmission Line Outage Duration ) of 1,86 hours then it can be said still in the performance target set PLN 5,54 hours, while for TLOF ( Transmission Line Outage Frequensi ) of 0,84 times then it can be said still in the target performance set by PLN of 1,96 times. The disturbance that occurred during the year 2017 caused by the equipment as much as 2 times with the old out 4,4 hours and the unattached load of 57,5 kWH. To minimize the amount of disturbance that occurs it is expected that the electricity provider increases the maintenance schedule and increases the knowledge of the disruption caused by the equipment so that the unencumbered energy can be minimized.